Upaya Membangun Personal Branding Prilly Latuconsina Dengan Citra Wanita Karir Melalui Akun Instagram @Prillylatuconsina96 - Sevia Yussinta Sari; Ratna Setyarahajoe; Muhammad Fadeli (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Instagram has become one of the tools used by public figures to build their self-image and strengthen their personal branding widely in the digital era. This study aims to analyze how Prilly Latuconsina's efforts to build her personal branding with the image of a career woman through her Instagram account @prillylatuconsina96. Prilly Latuconsina as an actress uses Instagram not only as an entertainment medium, but also as a communication strategy to display her professionalism, independence, and the values ​​of a modern career woman. This study uses a descriptive qualitative method through observation and documentation of content in the form of uploaded photos, videos, and captions using Peter Montoya's eight pillars of personal branding theory. The results show that Prilly Latuconsina consistently displays professional activities, discipline, commitment to work, and inspirational messages that can strengthen her image as an independent and high-achieving young career woman. Prilly Latuconsina has succeeded in building a strong and relevant personal branding for the younger generation, especially women. This study confirms that Instagram is an effective medium in shaping the self-image of public figures in the digital era.